Index Selection Preference and Weighting for Uncertain Network Sentiment Emergency - Qiansheng Zhang; Fuchun Liu; Bailin Xie; Yirong Huang (Institute of Advanced Engineering and Science, 2013)
To more effectively cope with the network public sentiment emergency involved many interval-valued warning indexes, we present a new method of early warning index selection and weight assignment for uncertain network public sentiment emergency decision-making. By using a new interval fuzzy AHP, the interval weight of each early warning index of network public sentiment emergency can be obtained. Then by means of the weighted aggregation values of all the emergency warning indexes, we can rank the severity of every network public sentiment emergency and select the most severe one. Finally, a numerical example is given to illustrate the application of the proposed method of warning index selecting and weighting to uncertain network public sentiment emergency decision. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1898